Exposure of neonatal rats to maternal cafeteria feeding during suckling alters hepatic gene expression and DNA methylation in the insulin signalling pathway - Daniel, Zoe; Akyol, Asli; McMullen, Sarah; Langley-Evans, Simon C, (Springer, 2013)
Nutrition in early life is a determinant of lifelong physiological and metabolic function. Diseases that are associated with ageing may, therefore, have their antecedents in maternal nutrition during pregnancy and lactation. Rat mothers were fed either a standard laboratory chow diet (C) or a cafeteria diet (O) based upon a varied panel of highly palatable human foods, during lactation. Their offspring were then weaned onto chow or cafeteria diet giving four groups of animals (CC, CO, OC, OO n=9-10). Livers were harvested 10 weeks post-weaning for assessment of gene and protein expression, and DNA methylation. Cafeteria feeding post-weaning impaired glucose tolerance and was associated with sex-specific altered mRNA expression of peroxisome proliferator activated receptor gamma (PPARg) and components of the insulin-signalling pathway (Irs2, Akt1 and IrB). Exposure to the cafeteria diet during the suckling period modified the later response to the dietary challenge. Post-weaning cafeteria feeding only down-regulated IrB when associated with cafeteria feeding during suckling (group OO, interaction of diet in weaning and lactation P=0.041). Responses to cafeteria diet during both phases of the experiment varied between males and females. Global DNA methylation was altered in the liver following cafeteria feeding in the post-weaning period, in males but not females. Methylation of the IrB promoter was increased in group OC, but not OO (P=0.036). The findings of this study add to a growing evidence base that suggests tissue function across the lifespan a product of cumulative modifications to the epigenome and transcriptome, which may be both tissue and sex-specific.